WHAT LEADS TO A POSITIVE RETIREMENT EXPERIENCE: A FOCUS ON RETIREMENT EXPECTATIONS, NORMS, AND RESOURCES. (11th November 2018) - Fraire, N; Infurna, F J; Wang, M
Abstract: Retirement is a major life transition in late adulthood that is particularly important to study during the current demographic graying of society, because people are spending more years in retirement and more people are entering the retirement years than ever before in history. The goal of this symposium is to bring together a collection of papers that target factors that are associated with better subjective and financial well-being in retirement. Hershey and colleagues examine predictors of pre-retirement expectations regarding retirement income and find country-level differences in anticipated post-retirement financial well-being. Fraire and Infurna use longitudinal panel survey data from Australia to track subjective well-being before and after retirement and find that retiring on-time relatively to retirement age norms as well as within one's expectations is associated with better subjective well-being following retirement. Henning and colleagues use longitudinal panel survey data from Sweden to examine the extent to which subjective well-being and the three basic psychological needs of relatedness, autonomy and competence co-vary across the retirement transition; they find evidence for changes in how autonomy and competence contribute to subjective well-being before and after retirement. Fisher and colleagues use panel data from the Health and Retirement Study to investigate how meaningfulness of work relates to antecedents and outcomes of retirement, including retirement expectations, retirement plans and behavior, and retirement adjustment. The discussion by Dr. Wang will integrate the four papers, highlight the importance of various factors leading to better adjustment in retirement, and consider future routes of inquiry.